2014
DOI: 10.3390/molecules190710189
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profiles and Antioxidant Properties of Young Wines Made from Yan73 (Vitis vinifera L.) and Cabernet Sauvignon (Vitis vinifera L.) Grapes Treated by 24-Epibrassinolide

Abstract: Abstract:The grape berries of two varieties, Yan73 (Vitis vinifera L.) and Cabernet Sauvignon (CS) (Vitis vinifera L.) were treated with 0.40 mg/L 24-epibrassinolide (EBR), 1.00 mg/L brassinazole (Brz), and deionized water (control), at the veraison period. The EBR treatment significantly increased total phenolic content (TPC), total tannin content (TTC) and total anthocyanin content (TAC) of Yan73 and CS wines, whereas Brz treatment decreased TPC, total flavonoid content (TFC), TAC in the two wines. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In this work, the expression level of HbBRI1s was upregulated by ABA, BR and ETH, and was downregulated by GA and JA. Combined with microarray analysis and qRT-PCR results in the rubber tree, we found that the expression of HbBRI1s and HbBAK1s in different tissues and various treatments shared differential functions, which were similar with those found in other species [ 52 , 53 , 57 , 58 ]. We assumed that the strong induction regulation mechanism appeared after 10 h with the ABA, BR and ETH treatment, after 6 h with the SA treatment, after 2 h with the GA treatment, and after 0.5 h with the JA treatment.…”
Section: Discussionsupporting
confidence: 69%
“…In this work, the expression level of HbBRI1s was upregulated by ABA, BR and ETH, and was downregulated by GA and JA. Combined with microarray analysis and qRT-PCR results in the rubber tree, we found that the expression of HbBRI1s and HbBAK1s in different tissues and various treatments shared differential functions, which were similar with those found in other species [ 52 , 53 , 57 , 58 ]. We assumed that the strong induction regulation mechanism appeared after 10 h with the ABA, BR and ETH treatment, after 6 h with the SA treatment, after 2 h with the GA treatment, and after 0.5 h with the JA treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Brix values were determined with a hand-held digital Atago PAL-1 meter (Atago Co. Ltd., Tokyo, Japan) and the pH was measured with a Mettler Toledo FE20 Desktop pH Meter (Mettler Toledo Instruments Co. Ltd., Shanghai, China) [31]. The TPC was determined by the method by Xu et al and the TAC was estimated according to the pH differential method by Meng et al [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…In the ABTS assay, according to the method described by Xu et al [48], 7 mM ABTS solution and 2.45 mM potassium persulphate aqueous solutions were mixed and then left standing in the dark at room temperature for 24 h before being used. Five μL of the original extracts were added to 995 μL ABTS solution.…”
Section: Methodsmentioning
confidence: 99%